Sosialisasi Hilirisasi Untuk Membangun Ekonomi Bangsa Di Kelurahan Sidorame Barat 2, Medan Perjuangan - Sugiharto, Bambang; Harkim, Harkim; Simanungkalit, Rejekia; Andriani, Maya; Marwan, Agus (Universitas Pahlawan Tuanku Tambusai, 2024)
Industrial downstreaming is one of the government's strategies in strengthening the national economy by optimally utilizing natural resources and increasing added value. This program aims to increase the understanding of the community of Sidorame Barat 2 Urban Village, Medan Perjuangan, about the concept of downstreaming and its impact on the local and national economy. Through a socialization and education approach, this activity is expected to build community awareness of the importance of downstreaming in promoting sustainable economic growth. The results of this activity showed the community's enthusiasm to participate in downstream initiatives in their area as well as their increased understanding of the contribution of downstream in the nation's economic development.